Kearifan Lokal Makanan Tradisional: Tinjauan Etnis dan Fungsinya pada Tradisi Ngaturin di Desa Sembiran, Buleleng, Bali - Damiati, Damiati; Suastra, I Wayan; Arnyana, Ida Bagus Putu (JURNAL GASTRONOMI INDONESIA, 2024)
Abstrak This research aims to identify dishes in the ngaturin tradition in Sembiran Village, Tejakula, Buleleng, Bali. The data collection techniques used were interviews and observation. The data analysis used is descriptive qualitative. The research results show three things. 1). The ngaturin ceremony is a ritual that must be carried out by all married men, carried out to provide compensation for the holy water received (the basis for the request for a hug) as well as to ask for a good place for the ancestors. What is unique is that the dish is served using beef, where most Hindu people do not consume processed beef. 2). The dishes served in the ngaturin tradition consist of the main dish, namely white rice, side dishes arranged in megibung covered with banana leaves, arranged starting with rice and side dishes. Side dishes with soup are served with a drizzle. 3). Food in the ngaturin tradition can only be eaten at the arrange temple and in the homes of people who carry out this tradition. Dishes cannot be taken outside the house or Sembiran village and can only be enjoyed for 1 day. If anything remains, it must be thrown away and buried. If the dish is taken outside the village, it will bring disaster to the community. The meaning is gratitude to God for his request that his ancestors be in the best place. Food is enjoyed in a megibung manner which means togetherness, mutual respect and respect which contains philosophical, anthropological, sociological and psychological values.